Quando as lembranças doem: A casa da infância em Vermelho amargo, de Bartolomeu Campos de Queirós - Da Silva, Marcela Verônica [UNESP] (FapUNIFESP (SciELO), 2016)
Bartolomeu Campos de Queirós? last work, the novel Vermelho Amargo (2011) draws attention to both form and content. The dark red cover of the first edition by Cosac Naify, seems empty of life, which is normally signaled by this color, and points to the painful content of the narrative, a mixture of poetic memorial prose and autobiographical writing. Childhood images appear as unhealed wounds, and the reader has the opportunity to unveil the power of the poetic verb by facing these wounds. Thus, the objective of this article is firstly to discuss the autobiographical writing and the memorial narrative and, secondly, to analyze the author?s work in order to point to the image of the house as a construct of consciousness. These themes will be examine through the theoretical contribution of Gaston Bachelard, in particular his reflections on the psychology of temporal phenomena and the poetics of space in regards to the original house, considered the formative place of subjectivities of being, and that, according to Bachelard, is always revisited, especially in moments of solitude.
When memories hurt: The childhood house in Vermelho amargo by Bartolomeu Campos de Queirós
Keywords: Autobiography; Bartolomeu Campos de Queirós; Childhood; Home; Memory